Factors influencing nursing students’ continued success in a baccalaureate nursing program in Indonesia - Christine L. Sommers; Grace Solely Houghty; Rijanto Purbojo; Innocentius Bernarto (Belitung Raya Foundation, Indonesia, 2022)
Background: Holistic admission processes are needed to promote diversity in nursing students. Previous research had identified different variables related to the average grade point at the end of the first semester. There is a need to examine if those variables are associated with ongoing student success. Objective: The purpose of this study was to analyze experience, attributes, and academic variables for an association with nursing student success. Student success was defined as being an active student at the end of the first year and at the end of the second year of a baccalaureate nursing program in Indonesia. Methods: Binary logistic regression analysis was used to determine what relationship, if any, the variables had with student success, measured at the end of the first and second academic years. The data of 341 nursing students enrolled in August 2018 was analyzed. Results: The variables accounted for 40.3% of the variance at the end of the first year and 24.3% of the variance at the end of the second year. There was a significant (p < .05) relationship between being enrolled at the end of the first year and 1) academic variables of first semester grade point average and the admission score of Raven’s Advanced Progressive Matrices, and 2) attribute variables of reason for entering nursing and brief calling presence scale. A significant relationship was found between being enrolled at the end of the second year and the attribute variable of grit score. No variables had a strong correlation with other variables. Conclusion: Holistic admission processes and promoting student success can create the future of the nursing workforce. Improving the diversity in admitted nursing students will enhance the diversity in the nursing workforce. To promote the success of all students, a variety of support interventions will need to be developed. As students’ calling and grit may play a role in student success, a better understanding is needed. In addition, more research is needed to explore how developing calling and grit throughout the nursing program can impact student success.